No Benefit of Prophylactic Surgical Drainage in Combined Liver and Kidney Transplantation: Our Experience and Review of the Literature - Vincenzi, Paolo; Gaynor, Jeffrey J.; Chen, Linda J.; Figueiro, Jose; Morsi, Mahmoud; Selvaggi, Gennaro; Tekin, Akin; Vianna, Rodrigo; Ciancio, Gaetano (Frontiers in Surgery, 2021)
Background: Contrasting results have emerged from limited studies investigating the role of prophylactic surgical drainage in preventing wound morbidity after liver and kidney transplantation. This retrospective study analyzes the use of surgical drain and the incidence of wound complications in combined liver and kidney transplantation (CLKTx). Methods: A total of 55 patients aged > 18 years were divided into two groups: the drain group (D) (n= 35) and the drain-free group (DF) (n= 20). Discretion to place a drain was based exclusively on surgeon preference. All deceased donor kidneys were connected to the LifePort Renal Preservation Machine® prior to transplantation, in both simultaneous and delayed technique of implantation of the renal allograft. The primary outcome was the development of superficial/deep wound complications during the study follow-up. Secondary outcomes included the development of delayed graft function (DGF) of the transplanted kidney, primary non function (PNF) and early allograft dysfunction (EAD) of the transplanted liver, graft failure, graft and patient survival, overall postoperative morbidity rate and length of hospital stay. Results: With a median follow-up of 14.4 months after transplant, no difference in the incidence of superficial/deep wound complications, except for hematomas, in collections size, intervention rate, PNF, EAD, graft failure and patient survival, was observed between the 2 groups. Significantly lower level of platelets, higher INR values, DGF, morbidity rates and length of hospital stay were reported postoperatively in the D group. Preoperative hypoalbuminemia and longer CIT were included in the propensity score for receiving a drain and were associated with a significantly higher rate of developing a hematoma post-transplant. Conclusions: Absence of the surgical drain did not appear to adversely affect wound morbidity compared to the prophylactic use of drains in renal transplant patients during CLKTx.